Resolution pattern for mass spectrometry imaging. (20th April 2015) - Fagerer, Stephan R.; Römpp, Andreas; Jefimovs, Konstantins; Brönnimann, Rolf; Hayenga, Gerd; Steinhoff, Robert F.; Krismer, Jasmin; Pabst, Martin; Ibáñez, Alfredo J.; Zenobi, Renato
Abstract : Rationale: Up to now, there is no 'gold standard' for determining the resolution of a mass spectrometry imaging (MSI) setup (comprising the instrument, the sample preparation, the sample and the instrument settings). A standard sample in combination with a standard protocol to define the MSI resolution would be desirable in order to compare the setups of different laboratories, and as a regular quality control/performance check. Methods: Microstructured resolution patterns were fabricated that can be used to determine the spatial resolution in MSI experiments, down to the range of a few µm. Two different strategies were employed, one where the resolution pattern is laser machined into a thin metal foil, which can be placed over a sample to be imaged, and a second one where hydrophilic grooves are machined into an omniphobic coating covering the surface of an indium tin oxide covered glass slide. When dragging a sample solution over the slide's surface, the sample is automatically retained in the hydrophilic grooves, but repelled by the omniphobic coating. Results: The technology was tested on a commercial matrix‐assisted laser desorption/ionization (MALDI) imaging instrument, and a spatial resolution in the vicinity of 50 µm was determined. The finest features of the microstructured resolution patterns are compatible with the best spatial resolution of MALDI imaging systems available to date. Conclusions: The use of metal resolution grids or glass slides with hydrophilic/hydrophobic structures is suitable for the convenient determination of the resolution limit of the MALDI imaging instrument as determined by its hardware. These structures are straightforward both to produce and to use. Copyright © 2015 John Wiley & Sons, Ltd.